Primary blood current infections associated with catheters in the Neonatal ICU (Research, Society and Development, 2022)
Objective: To report the primary bloodstream infections associated with central catheters that occurred during a follow-up performed by a nurse in a Neonatal ICU. Methodology: Descriptive ecological study on primary bloodstream infections associated with central catheters that occurred during a follow-up performed by a nurse in a Neonatal ICU, from January to June 2017. Data were collected from the Epimed Monitor system and through form on the Treatment of Health Care-Related Infections. Results and discussion: During the period evaluated, 95 (48.47%) newborns used a total of 122 central catheters. The incidence density of Primary Infections Associated with the use of central catheters in the 1st Semester of 2017 was a total of 8 events. As for the microorganisms evidenced in blood culture, we had a prevalence of Klebsiela Pneumonie, followed by Staphylococcus Aureus. Final considerations: It is inferred that the safety of the newborn in the Neonatal Intensive Care Unit should be one of the scopes of public policies for patient safety, with the purpose of avoiding risks to their health and promoting their well-being and quality of life. Therefore, for this objective to be achieved, the scientific and technical improvement of health professionals in favor of neonatal health is necessary.